Optimizing coordinating contract design to support reverse logistics practices: A literature review - REN, NA (2017)
RL has received considerable attention due to its functions in creating profits from recycling and making contributions to sustainable development of environment. Several related reviews have been done to reverse logistics in recent years, but few are specialized in coordination contract which is a kind of mechanism that can improve operation efficiency. In order to enrich the research in this field, this paper firstly investigates the recent development in researches regarding to coordination contract in terms of reverse logistics structure, uncertainties in implementation, channel leadership and utilization of contracts. Also, basic introduction about current reverse logistics applications is shown first to give a brief introduction to how reverse logistics is operated. Finally, research gaps and future research opportunities are identified. It is believed that the review here can provide a clear insight into what is a reverse logistics and how coordination contract is used to improve channel’s or individual’s performance. Also, the discussion and analysis provided can help researchers enhance their work in the future.